2016
DOI: 10.1002/art.39725
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐130b Ameliorates Murine Lupus Nephritis Through Targeting the Type I Interferon Pathway on Renal Mesangial Cells

Abstract: Objective. Type I interferon (IFN) is a critical pathogenic factor during the progression of lupus nephritis (LN). Although microRNAs (miRNAs) have been shown to control the IFN response in immune cells in LN, the role of miRNAs in resident renal cells remains unclear. We undertook this study to investigate the role of microRNA-130b (miR-130b) in the IFN pathway in renal cells as well as its therapeutic effect in LN.Methods. Kidney tissues from patients and (NZB 3 NZW)F1 lupus-prone mice were collected for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 54 publications
3
42
0
Order By: Relevance
“…IRF1 is a transcription factor that is activated by type I IFN signaling and is important for development of (32), and prediction of treatment response in lupus nephritis(33). Importantly, IRF1 has been identified as a central regulator of target genes in lupus monocytes(34) and has been reported as a transcription factor of caspase-1(35, 36).…”
Section: Resultsmentioning
confidence: 99%
“…IRF1 is a transcription factor that is activated by type I IFN signaling and is important for development of (32), and prediction of treatment response in lupus nephritis(33). Importantly, IRF1 has been identified as a central regulator of target genes in lupus monocytes(34) and has been reported as a transcription factor of caspase-1(35, 36).…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes from active lupus patients expressed significant lower miRNA-302d, which is associated with increased interferon regulatory factor (IRF)-9 both in patients and pristine induce lupus model [59]. Moreover, in kidney tissues of lupus patients and mice model, renal mesangial cells express much lower miRNA-302d, which is negatively correlated with its target gene IRF-1 [60]. Cheng, et al found that miRNA-451a increased in both spleen and thymus tissues in lupus mice model.…”
Section: Extracellular Rna and Slementioning
confidence: 99%
“…Although the investigators did not identify which cells synthesized type I IFN, it is possible that mesangial cells contribute 49 . Regulation of type I IFN in mesangial cells is mediated at least in part by microRNA (miR)-130b, and miR-130b expression is decreased in renal specimens from patients and mice with LN 50 .…”
Section: Recent Knowledge On Renal Inflammation In Lupus Nephritismentioning
confidence: 99%